DETERMINAN PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA PASCA KRISIS KEUANGAN GLOBAL - Muh. Ruslan Abdullah (MUAMALAH, 2014)
Variations of Islamic Banking Profitability as measured by the post-crisis ROA is able to be explained by the variables FDR, NPF, CAR. and BOPO 79% while the rest is explained by other variables that are not intended in this model. Variables simultaneously FDR, NPF, CAR and BOPO effect on ROA Islamic banking. Partially only variable BOPO effect on ROA. While the variables FDR, NPF, and CAR has no effect on ROA of Islamic banking.